A Retrospective Overview of Indian Journal of Finance Between 2011 and 2022 - Krishna Ludhani, Kamal; Kumar, Sanjay (Indian Journal of Finance, 2023)
Purpose : This study was conducted to provide a comprehensive overview of the significant influences of Indian Journal of Finance publications over the past 11 years. This study analyzed the journal’s publication and citation structures and identified the top authors, institutions, and countries contributing to its content. Methodology : We analyzed the journal’s bibliographic data using VOSviewer, Gephi, and Bibliometrix-R. Through bibliographic coupling and keyword cooccurrence networks, common research themes were identified. In addition, three-field plots were generated to visualize relationships among authors, countries, institutions, and keywords. Findings : The analysis revealed 10 significant research themes from the journal’s publications. These themes encompassed various areas of study, including (a) volatility in the Indian stock market, (b) corporate governance and capital structure, (c) financial inclusion, (d) evaluation of bank performance and efficiency, (e) dividend policy and shareholders’ wealth, (f) behavioral finance, (g) macroeconomic variables and the Indian economy, (h) asset pricing and market efficiency of stock markets, (i) initial public offer pricing and analysis, and (j) mutual funds. Practical Implications : This study provided valuable insights into the influential research themes within the analyzed journal’s publications by conducting a comprehensive bibliometric analysis. The findings contributed to understanding the journal’s knowledge landscape and could serve as a foundation for future research in related fields. Originality : This study offers a detailed retrospective examination of the Indian Journal of Finance from 2011 to 2022. This analysis provided valuable insights into the journal's evolution and contributions within the specified period.